2016
DOI: 10.1515/rjdnmd-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c as a Predictor of Dyslipidemia in Algerian Type 2 Diabetic Patients

Abstract: Background and Aims: The aim of our study was to test whether TG, as compared to patients with HbA1c ≤ 7.0% (p<0.05 for all). HDL-C levels didn't differ between the two groups (p= 0.322). Conclusions: The study suggests the usefulness of HbA1c as a predictor of dyslipidemia for screening of type 2 diabetic patients at high risk of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…The 46.3% mixed dyslipidemia detected in Northwestern Nigeria is also lower than this study but somehow equivalent to that of Southern Ethiopia. However, the existing finding is in agreement with findings of other studies which have shown 81.1-94% dyslipidemia and as high as 57.3-75% mixed occurrence over the globe [37,[45][46][47][48][49]. Despite such high prevalence dyslipidemia is quite amendable.…”
Section: Plos Onesupporting
confidence: 91%
“…The 46.3% mixed dyslipidemia detected in Northwestern Nigeria is also lower than this study but somehow equivalent to that of Southern Ethiopia. However, the existing finding is in agreement with findings of other studies which have shown 81.1-94% dyslipidemia and as high as 57.3-75% mixed occurrence over the globe [37,[45][46][47][48][49]. Despite such high prevalence dyslipidemia is quite amendable.…”
Section: Plos Onesupporting
confidence: 91%
“…13 Penelitian ini juga hampir sama dengan penelitian Aicha Laissaoui et al, HbA1c sebagai prediktor dislipidemia. 14 Glukosa dan asam lemak adalah dua sumber energi terbesar dalam tubuh. Gangguan salah satu unsur tersebut akan mempengaruhi metabolisme lainnya, misalnya pada DM gangguan metabolisme gula dihubungkan dengan dislipidemia.…”
Section: Pendahuluanunclassified